Centromedian thalamic nuclei deep brain stimulation and Anakinra treatment for FIRES – Two different outcomes. (September 2019) - Sa, Mario; Singh, Rinki; Pujar, Suresh; D'Arco, Felice; Desai, Nivedita; Eltze, Christin; Hughes, Elaine; Al Obaidi, Muthana; Eleftheriou, Despina; Tisdall, Martin; Selway, Richard; Cross, J. Helen; et al.
Abstract: Febrile infection-related epilepsy syndrome (FIRES) is a severe epilepsy disorder that affects previously healthy children. It carries high likelihood of unfavourable outcome and putative aetiology relates to an auto-inflammatory process. Standard antiepileptic drug therapies including intravenous anaesthetic agents are largely ineffective in controlling status epilepticus in FIRES. Deep brain stimulation of the centromedian thalamic nuclei (CMN-DBS) has been previously used in refractory status epilepticus in only a few cases. The use of Anakinra (a recombinant version of the human interleukin-1 receptor antagonist) has been reported in one case with FIRES with good outcome. Here we describe two male paediatric patients with FIRES unresponsive to multiple anti-epileptic drugs, first-line immune modulation, ketogenic diet and cannabidiol. They both received Anakinra and underwent CMN-DBS. The primary aim for CMN-DBS therapy was to reduce generalized seizures. CMN-DBS abolished generalized seizures in both cases and Anakinra had a positive effect in one. This patient had a favourable outcome whereas the other did not. These are the first reported cases of FIRES where CMN-DBS has been used. Highlights: Centromedian thalamic deep brain stimulation plays a role in FIRES as a treatment for reducing generalized seizure burden. In view of the proposed autoinflammatory aetiology for FIRES Anakinra should be considered as a possible treatment option. CMN-DBS did not have a lasting effect on focal seizures burden.